An estimation of power output and work done by the human triceps surae musle-tendon complex in jumping - Bobbert, Maarten F.; Huijing, Peter A.; van Ingen Schenau, Gerrit Jan (Journal of biomechanics, 1986)
In explosive movements involving the lower extremity elastic recoil and transportation of power from knee to ankle via m. gastrocnemius allow power output about the ankle to reach values over and above the maximum power output of the plantar flexors. The object of this study was to estimate the relative power and work contributions of these two mechanisms for the push-off phase in one-legged jumping. During jumps of ten subjects ground reaction forces and cinematographic data were recorded. The data were used for a kinematic and kinetic analysis of the jumps yielding, among other variables, the velocity with which origins of m. soleus and m. gastrocnemius approach insertion ( V OI ), and net power output about the ankle ( P A ). V OI of m. soleus and m. gastrocnemius were imposed upon a model of the muscle-tendon complex of m. triceps surae, and power contributions of muscle fibers ( P fibers ), tendinous structures ( P tendon ), and transportation ( P transported ) were calculated. During the last 150 ms before toe-off, P A was found to increase rapidly and to attain an average peak value of 1790 W. The curve obtained by summation of P fibers , P tendon and P transported closely resembled that of P A . On the instant that the latter peaked (50 ms before toe-off) P fibers and P tendon of m. triceps surae contributed 27 and 53% respectively, and P transported contributed 20%. Closer investigation of the transformation of rotations of body segments into translation of the mass center of the body revealed that during the last 90 ms before toe-off a high energy output about the ankle was required for maximization of the amount of external work. According to the model muscle fibers, tendinous structures and transportation accounted for 30, 45 and 25%, respectively, of the total amount of work done during these last 90 ms (105 J on the average). It is concluded that elastic recoil and transportation are very important for jumping performance.